2013
DOI: 10.17221/141/2012-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Determining fluctuations and cycles of corn price in Iran

Abstract: Abstract:Corn is the third important agricultural product. It is an important input in the poultry production and the basic elements of edible oil, starch, glucose, and raw material in industrial production of ethanol and some other products. Th e aim of this study is to fi nd strategies to avoid price volatility, hence, the harmonic method has been used to investigate the corn price cycle and the GARCH model has been used to investigate its fl uctuation. Th e harmonic method results showed long-term cycles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…This condition is allegedly due to the slow flow of information (asymmetric information) from the market in Jakarta to the Kupang city and the market in Kupang district, as well as infrastructure and commodity cycle constraints in the form of selling time and business patterns. According to Fakari, et al, (2013) in the study of fluctuations and cycles of prices of agricultural commodities (corn) in Iran, finding that each commodity often has its own price movement cycle.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is allegedly due to the slow flow of information (asymmetric information) from the market in Jakarta to the Kupang city and the market in Kupang district, as well as infrastructure and commodity cycle constraints in the form of selling time and business patterns. According to Fakari, et al, (2013) in the study of fluctuations and cycles of prices of agricultural commodities (corn) in Iran, finding that each commodity often has its own price movement cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Fakari et al (2013) constructed a GARCH model and found that the corn price fluctuation cycle was 21 months. They also discovered that short-term volatility in corn prices could lead to greater fluctuations in future futures prices, and that futures contracts are an effective tool for controlling corn price volatility [ 3 ]. Zhou et al (2015) used quarterly price data from 2004 to 2014 to build an ARMA model for forecasting the prices of Chinese cabbage, cucumbers, and tomatoes.…”
Section: Background and Relevant Literaturementioning
confidence: 99%
“…The average unconditional volatility of international price in grain markets almost rose 80 percent, this price volatility usually transmitted to grain markets in developing countries (Ceballos et al, 2015). Price volatility has a drastic impact on some actors such as producers, consumers, investors, and government (Fakari et al, 2013).…”
Section: Introductionmentioning
confidence: 99%